ผลของสารปรับสภาพพื้นผิวที่มีต่อความแข็งแรงดัดขวางในการซ่อมฐานฟันปลอมอะคริลิกเรซิน - นงลักษณ์ เกรียงไกรเกษม (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Objective: To evaluate the effect of the selected chemical surface treatment agents on the flexural strength of heat-cured acrylic resin when repaired with self-cured acrylic resin. Materials and Methods: One hundred heat cured acrylic resin specimens were prepared according to ISO1567 and randomly divided into 10 groups ; positive and negative control (group 1 and 2) and eight experimental groups. Group 2-10 were cut in the middle and beveled 45 degree. Group 3 and 4 were treated with liquid part of Unifast trad® for 5 and 180 seconds respectively. Group 5 was treated with Rebase II adhesive® according to the manufacturer. Group 6-10 were treated with methyl acetate, methyl formate and methyl acetate -methyl formate solutions for 15 seconds. Then repaired with self-cured acrylic resin. A three-point loading test was performed by using Universal testing machine (INSTRON UK). One-way ANOVA and post hoc Tukey’s analysis at p<.05 were used for statistical comparison. Failure analysis was also recorded for each specimen. Result: The flexural strength of group 4-10 were significantly greater than Group 2 (p<.05). The flexural strength of group 5-10 were no significant difference (p>.05). All fractured specimens in group 6-10 showed 100% cohesive failure while group 2-5 showed cohesive failure 10, 40, 60 and 60% respectively. Conclusion: Treating surface with methyl acetate, methyl formate and methyl acetate -methyl formate solutions at various concentrations significantly increased flexural strength of heat-cured acrylic denture base resin when repaired with self-cured acrylic resin.